Revision of the genus Lethierium Dlabola, 1980 (Hemiptera: Auchenorrhyncha: Issidae), with description of two new species from Central Morocco - Gnezdilov, Vladimir M. (Zootaxa, 2022)
North-African planthopper genus Lethierium Dlabola, 1980 is revised. Lethierium cedricolum (Dlabola, 1989), L. juniperi (Bergevin, 1915), and L. reiberi (Lethierry, 1878) are redescribed, with new records provided. Two new species are described from Central Morocco—L. carinatum sp. nov. from Middle Atlas Mountains and L. grandilobum sp. nov. from High Atlas Mountains. L. juniperi is recorded for the first time from Morocco. A key to species of the genus is provided. The phylogenetic relationships of Lethierium Dlabola within the subfamily Hysteropterinae are discussed.